Islamic Legal Perspective on Data of Child Victims of Sexual Violence: A Case Study of the Indonesia’s Court - Gurusi, La; Mansyah, Muh Sutri; Lee, Kirsty; Purnamasari, Yety; Alfajar, Subhan (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
The Case Tracking Information System (SIPP), established by the Supreme Court, is designed to facilitate the tracking of legal cases. However, concerns have arisen regarding data leakage of victims of sexual violence. This study seeks to analyse and evaluate the protection of personal data of victims of sexual violence published in the SIPP Court, particularly from an Islamic law perspective. Employing a socio-legal research method, the study integrates case, statutory, and conceptual approaches. Primary legal materials include laws and regulations relevant to victim protection, while secondary legal materials are sourced from relevant journals, books, and literature. The analysis was performed using a descriptive technique with grammatical and systematic interpretations. The results of the study show that five laws (Witness and Victim Protection Law, Sexual Violence Crime Law, Personal Data Protection Law, Juvenile Criminal Justice System Law, and Child Protection Law) regulate victim confidentiality to prioritise the best interests of children as the next generation of the nation. Despite these legal provisions, practical discrepancies persist. For example, in the SIPP of the Baubau District Court, sensitive details such as victims’ names are accessible, whereas the Aceh District Court only displays anonymised data, using aliases like